Dynamics of social change and perceptions of threat - Frie, Ewald; Kohl, Thomas; Meier, Mischa (Mohr Siebeck, 2018)
Warum verändern sich Dinge zu bestimmten Zeiten und nicht zu anderen? Die Beiträge in diesem Band betrachten diese Frage aus der Perspektive der Bedrohung. Selbstalarmierungen aus Gesellschaften oder sozialen Gruppen heraus öffnen Möglichkeitsfenster für Wandel – der oft nicht so verläuft, wie die Urheber der Alarmierung wünschen. Einmal bedroht, werden soziale Ordnungen, die zuvor als gegeben hingenommen wurden, sichtbar, verhandelbar und damit auch veränderbar. In fünf Sektionen behandeln die Beiträge ein weites Spektrum an bedrohten Ordnungen: Dürre und Flut in der modernen Welt, Aufstände in mittelalterlichen Städten, antike Glaubenssysteme sowie heutige organisierte Kriminalität und Protest. Alarmierung und Bedrohung, so zeigt sich, ermöglichen Analyse und Vergleich schnellen und überraschenden sozialen Wandels in vielen Gesellschaften.InhaltsübersichtEwald Frie/Mischa Meier: Dynamics of Social Change and Perceptions of Threat. An Introduction I. Framing Situations of Social Change and Threat in Contemporary Society Andreas Hasenclever: Introduction: Taking the Cultural Contexts of Group Mobilization Seriously – Holger Stritzel: The Travelling Concept of Organized Crime as a Threat to Political and Social Orders – Jan Sändig: Framing Non-Violence: MASSOB and the Puzzling Non-Escalation of the Struggle for Biafra in Nigeria II. Urban Unrest, Power and the Internal Dynamics of Social Change, c. 1050–1550 Klaus Ridder: Introduction – Thomas Kohl: Violence, Power and Social Change: European Cities c. 1050–1120 – Hannah Skoda: Threatened Orders in Paris, Oxford and Heidelberg – Beatrice von Lüpke: The Nuremberg Shrovetide Plays and their Perception of Social (Dis-)Order III. Making Sense of Threat – Systems of Belief under Threat, c. 200–800 Sebastian Schmidt-Hofner: Introduction – Communication of Threat and the Construction of Meaning – Matthias Becker: Framing the Christians as Sophists in Porphyry's Contra Christianos – Phil Booth: Liturgification« and Dissent in the Crisis of the East Roman Empire (6th-8th Centuries) IV. Disasters and Social Change, 19th-20th c. Klaus Gestwa: Introduction – Anna Ananieva/Rolf Haaser: Coping with Floods: The Imaginary Community of the »Elegant World« and the Hungarian Flood Disaster of 1838 – Rebecca Jones: Understanding the Conundrum of Drought in Australia V. The End of Threat: Diverging perspectives on Social Change during the 'Sattelzeit' (c. 1750–1850) Renate Dürr: Introduction – Dennis Schmidt: 'Daß alles beym Alten bleibet' Josephinism and Religious Orders in Inner Austria – Fernando Esposito: The Two Ends of History and Historical Temporality as a Threatened Order
Keywords: Aufsatzsammlung; Geschichte; Ordnung; Bedrohung; Sozialer Wandel; Geschichte 500 v. Chr.-2018; Sozialordnung